Unraveling the electromagnetic interaction of a Bessel pincer light-sheet beam by a metamaterial PEMC sphere - Arfan, Muhammad; Alkhoori, Hamad M.; Hussein, Mousa; Althobaiti, Saad; Althobaiti, Ali (Frontiers in Physics, 2025)
The interaction of a Bessel pincer light-sheet beam (BPLSB) with a metamaterial perfect electromagnetic conductor (PEMC) sphere is analyzed using the generalized Lorenz–Mie theory (GLMT). The electric field of the BPLSB is expanded by utilizing the vector angular spectrum decomposition method (VASDM). The electromagnetic fields (incident and scattered) are reconstructed by utilizing the vector spherical wave functions (VSWFs) and expanded beam shape coefficients (BSCs). Implementing the boundary conditions (BCs) on a metamaterial PEMC sphere yields the unknown expansion coefficients of the scattered electromagnetic fields. Unlike earlier GLMT studies that used plane wave or simple Bessel beams, the BPLSB source for a metamaterial PEMC sphere is employed. To investigate the electromagnetic scattering dynamics, the impacts of various configuration parameters of BPLSB, like beam order and beam scaling parameter, in addition to electromagnetic admittance and size parameter of the PEMC sphere, are analyzed meticulously. The scattering characteristics of BPLSBs by a metamaterial PEMC sphere are numerically analyzed in terms of scattering efficiency and scattering intensity in the far-field/far-zone region. This work will aid in exploring scattering and propagation, electromagnetic radiation force and torque, optical manipulation, optical tweezers, and light-matter interactions.